PENGARUH KUALITAS LAYANAN PADA KOMITMEN KONSUMEN DAN LOYALITAS KONSUMEN - , M. Taufik Hidayat Siregar, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to analyze the influence of tangibles, reliability, responsiveness, assurance, and empathy of affective commitment, calculative commitment, and consumersâ loyalty